Paschim Himalaya ke mausam tatha him par jalvayu parivartan ka pratighat (MAUSAM, 2013)
The complex topographical features of the Indian sub continent such as the high Himalayan ranges have started showing the affects of global climate change. Himalaya modulates weather over the entire northern belt of the Indian sub-continent. It also influences the Western Disturbances (WDs) during winter over the region. Some recent trends in the parameters of weather and climate over the Western Himalayan region have been studied and explanations have been given in context of climate change over these regions. The studies show how the climate changes in long term period with reference to the total precipitation over the station locations of these regions. Data analysis of Western Himalaya shows significant variations in temperature and total precipitation trends in the past few decades. The results show negative Correlation Coefficients (CCs) between the mean maximum and mean minimum temperature with the fresh snowfall the different station locations over Western Himalaya. The possible effects of the climate change on the number of snowfall days over the Western Himalayan region have also been analyzed. There is clear sign of shrinking winter over the Western Himalaya. Necessary efforts have been directed to understand the science of climate change more in regional scale over this complex orographic region.